Plant regeneration of Brassica oleracea sub sp. italica (Broccoli) CV Green Marvel as affected by plant growth regulators - Ravanfar, Seyed Ali; Abdul Aziz, Maheran; Abdul Kadir, Mihdzar; Abdul Rashid, Azmi; Sirchi, Mohammad Hossein Torabi (Academic Journals, 2009)
Hypocotyls and shoot tips were used as explants in in vitro plant regeneration of broccoli (Brassica oleracea subsp. italica) cv. Green Marvel. The explants were excised from sterile germinated seedlings and placed on shoot induction medium containing basal salts of Murashige and Skoog (MS) and various concentrations of 6-benzylaminopurine (BAP) and α-naphthaleneacetic acid (NAA). The highest percentage of hypocotyl explant producing shoot (96.67%) and the highest mean number of shoots produced per hypocotyl explant (6.03) were obtained on 3 mgL-1BAP. Meanwhile, the highest percentage of shoot tip explant producing shoot (100%) and highest number of shoot produced per shoot tip explant (3.76) were recorded on 5 mgL-1 BAP. For rooting of shoots, NAA, indoleacetic acid (IAA) and indolebutyric acid (IBA) at 0, 0.2 and 1 mgL-1 were applied. Highest percentage of shoots with roots (100%) and highest mean number of roots produced per shoot (6.5) occurred on medium with 0.2 mgL-1 IBA, while the maximum root length (2.46 cm) was attained on MS medium without plant growth regulator (MSO). Plantlets were successfully acclimatized in potting medium containing peatmoss, perlite, and vermiculite (3:1:1).